Blue Ocean Classics - Kim, W.; Mauborgne, Renee (Ascent Audio, 2019)
W. Chan Kim and Renee Mauborgne changed the field of strategy and the language of business with their pathbreaking "blue ocean strategy," a model for creating uncontested markets that unlock new demand and new opportunities for growth. This book brings together three of their classic blue ocean strategy articles, all first published in Harvard Business Review. "Blue Ocean Strategy" highlights the distinct differences between market-competing (red ocean) and market-creating (blue ocean) strategy and what it takes to create the new markets of tomorrow. In "Red Ocean Traps," Kim and Mauborgne reveal the faulty assumptions that keep managers tethered to existing overcrowded markets (red oceans). "Blue Ocean Leadership" applies the concepts and analytic frameworks of blue ocean strategy to an innovative leadership approach that releases employees' untapped talent and energy while conserving their most precious resource-time. This collection is the ideal start, or refresher, for creating more blue oceans.